2016
DOI: 10.3748/wjg.v22.i11.3186
|View full text |Cite
|
Sign up to set email alerts
|

Melittin induces human gastric cancer cell apoptosisviaactivation of mitochondrial pathway

Abstract: Melittin can induce apoptosis of human gastric cancer (GC) cells through the mitochondria pathways, and it may be a potent agent in the treatment of human GC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(57 citation statements)
references
References 45 publications
3
53
0
1
Order By: Relevance
“…Overall the data suggested that MEL can synergize with TRAIL in the induction of HCC cell apoptosis by activating the TAK1-JNK/p38 pathway but inhibiting the IκBα kinase-NFκB pathway [57]. Another study tested the efficacy of MEL in gastric cancer and observed that the agent induces apoptosis in SGC-7901 cells [58]. The accumulated data suggested that MEL induces early apoptosis, induces ROS levels, and induced caspase-3 activity.…”
Section: Anticancer Effects Of Bv and Its-conjugatesmentioning
confidence: 99%
“…Overall the data suggested that MEL can synergize with TRAIL in the induction of HCC cell apoptosis by activating the TAK1-JNK/p38 pathway but inhibiting the IκBα kinase-NFκB pathway [57]. Another study tested the efficacy of MEL in gastric cancer and observed that the agent induces apoptosis in SGC-7901 cells [58]. The accumulated data suggested that MEL induces early apoptosis, induces ROS levels, and induced caspase-3 activity.…”
Section: Anticancer Effects Of Bv and Its-conjugatesmentioning
confidence: 99%
“…Melittin has been proposed as a promising agent for anticancer therapy. Reportedly, MEL is prominently involved in the regulation of multifarious cancers, exemplified by hepatocellular carcinoma, breast cancer, lung cancer, leukaemia, ovarian carcinoma, gastric carcinoma, and prostate cancer . A handful of mechanisms of MEL cytotoxicity have been highlighted in various types of cancer cells (ie cell cycle alterations, effect on proliferation and/or inhibition of growth, induction of apoptosis.)…”
Section: Introductionmentioning
confidence: 99%
“…The intrinsic apoptosis pathway is also called mitochondrial pathway or cytochrome c mediated pathway. Many studies have demonstrated that mitochondria play important roles in cell apoptosis [33,34]. Although there is no obvious morphological change for mitochondria, some channels on mitochondrial membranes are open during the process of cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%